The use of scintigraphy to study gastric emptying, motility and small intestinal transit in patients who have ingested a selection of common poisons - Adams, Bruce Keith (Division of Nuclear Medicine, 2018)
Poisoning is common and carries considerable morbidity and mortality. Two to three patients are admitted to the Emergency Unit at Groote Schuur Hospital every day with drug overdose. As absorption occurs in the small intestine the rates at which ingested poisons pass into and through the small bowel are important factors in determining the amount of poison potentially available for absorption. Although the effects of pharmacological doses of many drugs on gastric emptying and motility are known, information on the effects of higher doses is limited. I investigated patients who took overdoses of certain commonly used drugs to determine their effects on gastric emptying and motility and small intestinal transit. The study was divided into two parts. One hundred and four patients were studied in Part 1. These patients took overdoses of tricyclic antidepressants (n = 31), carbamazepine (n = 15), phenytoin (n = 12), paracetamol (n = 29) and opioid-paracetamol mixtures (n = 17). They received standard hospital management of which sorbitol was not a part. Part 2 consisted of sixty-one patients who had sorbitol added to their treatment. These patients had taken overdoses of the tricyclic antidepressants (n = 15), carbamazepine (n = 7), phenytoin (n = 8), paracetamol (n = 13) and opioid-paracetamol mixtures (n = 18). The effects of sorbitol on gastric emptying and small intestinal transit were evaluated. A third study-the paracetamol control test was done on 5 healthy volunteers. Each subject was studied twice; the first time after taking 1 G of paracetamol and the second time after no drug ingestion.